Environmental TEM Investigation of Electrochemical Stability of Perovskite and Ruddlesden–Popper Type Manganite Oxygen Evolution Catalysts. (20th November 2017) - Mierwaldt, Daniel; Roddatis, Vladimir; Risch, Marcel; Scholz, Julius; Geppert, Janis; Abrishami, Majid Ebrahimizadeh; Jooss, Christian
Abstract: The sluggish kinetics of the oxygen evolution reaction (OER) is a grand challenge for energy storage technologies. Several perovskites and other oxides of earth‐abundant elements are found to exhibit improved catalytic OER activity. However, less attention is paid to the electrochemical stability, an important factor for large‐scale application. The ongoing search for stable catalysts calls for characterizing active catalyst surfaces and identifying mechanisms of deactivation, activation, or repair. In situ techniques are indispensable for these tasks. This study uses environmental transmission electron microscopy on the highly correlated perovskite Pr1– x Ca x MnO3 and the Ruddlesden–Popper Pr0.5 Ca1.5 MnO4 as model electrodes to elucidate the underlying mechanisms of the stability trends identified on rotating ring disk electrodes. An electron beam at fluxes well below those that would cause radiation damage is used to induce positive local electrode potentials due to secondary electron emission, driving electrochemical reactions in H2 O vapor. The stability of the model systems increases with increasing ionic character of the MnO bond, while more covalent bonds are prone to corrosion, which is triggered by formation of point defects in the oxygen sublattice. Abstract : The stability of perovskite Pr1– x Ca x MnO3 and Ruddlesden–Popper Pr0.5 Ca1.5 MnO4 model oxygen evolution catalysts is investigated by environmental transmission electron microscopy. The electron beam drives electrochemistry in H2 O vapor. Stability trends found by ex situ techniques during oxygen evolution are complemented by direct microscopic insight. Corrosion of Pr0.7 Ca0.3 MnO3 is based on recrystallization by point‐defect‐induced strain and chemical decomposition.